Construcción de un cuerpo libre de pecados (2023)
"Construction of a Sin-Free Body" is a multimedia and transdisciplinary research and creative project aimed at creating a visual and plastic exhibition. Through various artistic mediums such as anecdotal writing, photography, installation, sculpture, video, and performance, this project seeks to demonstrate the liberation of my non-binary body and identity through art.